Low density lipoprotein interferes with intracellular signaling of monocytes resulting in impaired chemotaxis and enhanced chemokinesis. (15th March 2018) - Tjaden, Kerstin; Adam, Christina; Godfrey, Rinesh; Hanley, Peter J.; Pardali, Evangelia; Waltenberger, Johannes
Abstract: Background: Hypercholesterolemia (HC) is an important cardiovascular risk factor characterized by elevated low density lipoprotein-cholesterol (LDL-C) plasma levels. HC negatively affects monocyte function by reducing their chemotactic response towards different growth factors. We aimed to elucidate the molecular mechanisms by which LDL induces monocyte dysfunction. Methods and results: Human monocytes exposed to either native (nLDL) or oxidized LDL (oxLDL) in vitro showed reduced chemotactic responses towards vascular endothelial growth factor A (VEGFA) and monocyte chemotactic protein-1 (MCP-1), but displayed enhanced random migration (chemokinesis). Mechanistically, the exposure to LDL resulted in the activation of p38 mitogen-activated protein kinase (MAPK) and modulated MCP-1 and VEGFA-induced signaling in human monocytes. Furthermore, the aberrant p38 activation induced by oxLDL is due to the functional impairment of Dual Specificity Phosphatase-1 (DUSP-1). In the absence of LDL, the pharmacological inhibition of DUSP-1 alone was sufficient to recapitulate the accelerated chemokinetic and blunted chemotactic phenotype of monocytes. Finally, p38 MAPK inhibition in monocytes isolated from hyperlipidemic mice prevented the aberrant chemokinetic phenotype. Conclusions: Our data demonstrate that LDL induces monocyte chemokinesis of human monocytes by inducing mononuclear cell activation through the aberrant modulation of DUSP-1-p38/MAPK signaling axis. Moreover, our findings suggest that MCP-1/VEGFA-induced chemotaxis is reduced by LDL secondary to the impairment of ligand-induced signaling. These findings provide novel insight into hypercholesterolemia-associated vascular dysfunction and its potential involvement in the pathogenesis of atherosclerosis. Highlights: LDL impairs monocyte function by inducing non-specific activation of monocytes. LDL promotes chemokinesis but blunts growth factor-induced chemotaxis of monocytes. OxLDL suppresses DUSP-1 phosphatase activity thereby promoting p38 MAPK activation. Modulation of DUSP-1/p38 axis induced by LDL contributes to monocyte dysfunction. Targeting DUSP-1/p38 axis could be a novel strategy to reduce monocyte activation.